HAKIKAT DAN TEORI PERKEMBANGAN BAHASA DI SEKOLAH DASAR - Alia Candra; Silvina Noviyanti; Tsalitsin Istahwadza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Language learning in elementary school is the foundation for improving students' literacy skills, which include writing, reading, and arithmetic. Language not only helps people communicate, but also helps them think, interact with others, and learn. Language learning must be properly designed, organized, and tailored to the characteristics of students because they are undergoing significant cognitive and linguistic growth during the elementary school stage of development. This study describes language development theory and its implementation in literacy learning in lower elementary school grades using a qualitative descriptive approach. Data were analyzed by conducting research and describing the phases of children's language skill development. According to the results of the study, children language development progresses gradually and in line with their communication experiences. Reading skills improve from reading pictures to reading fluently, writing skills improve from free scribbling to copying meaningful writing, and numeracy skills improve from knowing concrete concepts to using number symbols. Therefore, literacy learning is very important for improving early literacy and has a major impact on future learning success. It is hoped that the results of this study will help educators create learning that is more communicative, contextual, and appropriate for the stages of language development.